The study results of the world collection of hullless barley according to grain quality in the south of the Rostov region - E. S. Doroshenko; E. G. Filippov; A. A. Dontsova; D. P. Dontsov (Зерновое хозяйство России)
The current paper has presented the study results of the collection varieties of hull-less spring barley according to grain quality indices (protein, starch, lysine and ß-glucan). The initial material for the for the varieties' study in the conditions of the south of the Rostov region were than 100 varieties and lines of hull-less barley developed in the Federal State Budgetary Scientific Institution “FRC All-Russian Institute of Plant Genetic Resources named after N. I. Vavilov”. The study was carried out in the crop rotation of the department of barley breeding and seed production of the FSBSI “Agricultural Research Center “Donskoy” in 2016-2018. The purpose of the study was to scrutinize quality indices of the hull-less barley varieties. The trials were carried out according to the Methodology of the State Variety Testing. The accounting area of the plot was 10 m2, the seeding rate was 450 germinating grains per 1 m2, the standard variety ‘Ratnik’ was sown in 20 numbers with single sequence. The sowing was carried out with the seeder Wintershteiger Plotseed S; the harvesting was conducted with the combine Wintershteiger-Classik. The qualitative indices were determined according to generally accepted GOST standards. During the study under contrasting weather conditions, there have been identified the samples with increased indices of protein, lysine, starch and ß-glucan. In 2016 the variety ‘Golozerny’ (RF) was characterized by a high content of lysine and ß-glucan. In 2018 the samples ‘K-3800’ (Ukraine) and ‘Nigohodaka’ (Japan) combined a high content of several indices. Throughout three years of study, according to seed protein percentage, there has been identified the sample ‘Nigohadaka’ (Japan), which showed consistently high values of this trait. According to starch content there has been identified the sample ‘CDC Dawn’ (Canada). During the years of study, it was possible to trace that there were the advantages of hull-less samples according to quality indices over the unhulled standard variety. There could be made the conclusion that hull-less barley can be used in hybridization to improve quality.